Aplicação da avaliação do ciclo de vida como critério de seleção para materiais utilizados em construções sustentáveis - Figueiredo, Camilla Furtado de (2017)
The construction industry is one of the largest sectors in the world. This activity consumes more raw material than any other, becoming the one that causes more impact to the environment. Even so, the human being lives and works in built environments. As an alternative, sustainability is a primary concept of application for world society. Due to their need, the buildings are being designed with a view to technological innovation and environmental improvement with the reduction of the levels of pollutants emitted and the environmental impacts generated. In this way, the search for more sustainable construction solutions is growing. As the Life Cycle Assessment (LCA) methodology includes the compilation of material and energy flows, ie evaluation of inputs, outputs and impacts of a product throughout it’s life cycle, it’s use has been progressively search for the choice of more sustainable materials to be applied in buildings. The LCA proved to be an important tool, applicable to designers, and efficient as a support tool in the selection of more sustainable building materials. The proposed methodology, guided by the architectural and structural design, evaluating the materials for each stage of construction made it possible to achieve the objectives of the research in an organized and easy to understand way. The exhaustive bibliographical and documentary review were important for defining the materials to be evaluated. In this way, the objective of this work is to use the LCA with application of SimaPro® software to evaluate the environmental impacts in a two-floor model residence, to be held at the Center of Alternative and Renewable Energies of the Federal University of Paraíba, at the level of Emission of kg CO2-eq per m3 as criterion of selection of the materials to be applied in sustainable constructions. For the above and the infrastructure, the traditional concrete, the base of Portland cement and the concrete based on Alkalinally Activated Material (AAM) were compared; for the masonry were compared blocks of concrete and blocks of red ceramics; finally, for the roofing structures, traditional concrete slabs were compared with an association of AAM slabs with ceramic tile and wood and roof garden. It was carried out the survey of the quantity of materials needed for its construction and used two alternative materials based on the LCA for each stage of service (supra and infrastructure, masonry and roof structures). The results showed that the use of LCA is an alternative to be considered in the choice of materials aiming at a construction with a lower environmental impact.